Il Concilio di Trento e l'indissolubilità del matrimonio: questioni ermeneutiche - Álvarez de las Asturias, Nicolás (Ius ecclesiae, 2015)
The Council of Trent offered an important contribution to the doctrine and canonical discipline of marriage. In particular, Trent affirmed marriage's indissolubility within a canon whose drafting resulted in a formula that has provoked doubts regarding its doctrinal value. This article addresses the criteria for interpreting the value of that Tridentine canon